Gemological features of diaspore in sodra—Milas (mugla) region - Hikmet Kinaci, Eyyüp; Ozturk, Alican (Frontiers in Earth Science, 2023)
Diaspore, is related to bauxite in terms of its formation mechanism. Diaspore is one of the gemstone quality stones used in jewelry and jewelry making. It is possible to come across gemstones in various regions of the world. In our country, there are gemstone deposits in all regions. In these deposits, diaspore crystals are considered very valuable. Within the scope of this study, it was aimed to determine the gemological features of the diaspore formations in Sodra (Milas-Muğla) and its surroundings, as well as to determine other minerals and their formation conditions. During the field studies carried out in the study area, diaspore crystals were encountered in the Milas-Sodra region, together with chloritoid and muscovite, within the metabauxite formations and in the altered zones close to the metabauxite limestone contact. Rock were classified as “muscovite-quartzschist”, “quartzschist” with grano-lepidoblastic texture, “mica-quartzschist” with lepidoblastic texture, “phyllite” with lepidoblastic texture, and “chlorite-epidote fels” with nematoblastic texture as a result of petrographic analyzes performed on the country rock samples. Main oxide, trace, and rare earth element analyses were performed on seven collected samples. The classification was made using the Al2O3-SiO2-Fe2O3 triangular variation and it was determined that bauxite samples were in the "ferric bauxite" and "bauxite" areas. SEM imaging and EDS analyzes were performed on the samples and according to this result, it was determined that the samples mainly contained O, Al, and Si. The data obtained as a result of Raman Spectroscopy were matched with the device's own data library and it was determined that the samples taken from the Sodra region were diaspore. In addition, according to the results of the FTIR analysis performed on the faceted sample taken from the Sodra region, it was seen that the samples were compatible with the reference standards and it was scientifically proven to be a diaspore crystal with gemstone quality.